Bananas, oil, and development: examining the resource curse and its transmission channels by resource type - Jann Lay; Toman Omar Mahmoud (Kiel Institute for World Economics (IfW), 2004)
This paper examines the resource curse and its transmission channels by resource type. We review and synthesize existing theories of the transmission channels of the curse. This synthesis suggests that (1) relating the transmission channels to the characteristics of different types of resources, and (2) considering how other country characteristics, such as institutional quality and policy outcomes, affect the impact of natural resource wealth on development, would improve our understanding of the functioning of the curse. We then assess these two aspects empirically and find different transmission channels to be relevant for different types of resources. Furthermore, we illustrate the interaction between other country characteristics and the curse.
http://hdl.handle.net/1902.1/12935
Keywords: O11; C21; O13; 330; Natürliche Ressourcen; Dutch Disease; Entwicklungskonvergenz; Banane; Erdölvorkommen; Schätzung; Welt